Development Instructional Media Based on Virtual Reality Assisted by The MilleaLab Application on Tourism Resources Material - Ningsih, Mega Prani; Novitasari, Nastiti; Ramadhan, Ilham Rohman; Nurdianti, Raden Roro Suci; Shaari, Mohammad Zohir Bin Ahmad; Hannah, Beth; Durgaryan, Alesa (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
VR technology is changing the world of education by providing immersive and interactive learning experiences. This study develops LaViGeo, a VR-based learning media designed using the MilleaLab application to enhance learning in tourism resource materials. This study follows the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. This study involved 21 students in the Geography of Transportation and Tourism course, selected randomly. Data were collected using a validation questionnaire for material and media experts, as well as a student response survey. The results is LaViGeo was very feasible and effective to use from expert assessments and through trials with students. The integration of multimedia elements, learning videos, 360-degree images and interactive features can be accepted by students for concept materials related to tourism geography. There are challenges in the form of direct integration of 360-degree YouTube videos and limited trials so that further research is needed regarding wider implementation and optimization.